2010
DOI: 10.1016/j.energy.2010.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Technoeconomic analysis of a methanol plant based on gasification of biomass and electrolysis of water

Abstract: Methanol production process configurations based on renewable energy sources have been designed. The processes were analyzed in the thermodynamic process simulation tool DNA. The syngas used for the catalytic methanol production was produced by gasification of biomass, electrolysis of water, CO2 from post-combustion capture and autothermal reforming of natural gas or biogas. Underground gas storage of hydrogen and oxygen was used in connection with the electrolysis to enable the electrolyser to follow the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(60 citation statements)
references
References 12 publications
0
60
0
Order By: Relevance
“…[70]. ** This emissions account for methanol production process and the emissions occurring with the utilization of methanol.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…[70]. ** This emissions account for methanol production process and the emissions occurring with the utilization of methanol.…”
Section: Figurementioning
confidence: 99%
“…Therefore, methanol production from renewable hydrogen would increase the energy consumption; however, a significant GHG reduction may be possible [22]. Clausen et al [70] used electrolytic H 2 in methanol production using the post combustion captured CO 2 . The alkaline electrolyzer is operated at 90°C and atmospheric pressure with an electricity consumption of 4.3 kWh/Nm 3 H 2 corresponding to an efficiency of 70% (LHV).…”
Section: Methanol From Co 2 and Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated several method to produce methanol from CO 2 (Clausen et al 2010). Figure 7 shows the developed model proposed with the result showed that biogas reforming combined with water electrolysis gave the best methanol exergy efficiency up to 72% with specific methanol cost in range of 11.8-25.3 €/GJ exergy .…”
Section: Figure 6: Bloc Diagram Of the Process From Van-dal And Boualloumentioning
confidence: 99%
“…Carbon capture technology has been deployed and the utilization of CO 2 has been studied (Editorial 2015). CO 2 can be utilized for producing methane (Collet, et al 2017), methanol (Clausen, et al 2010), and other substances.…”
Section: Introductionmentioning
confidence: 99%